G34 Integrating elements of undergraduate curriculum learning. (27th April 2015) - Bell, A; Corkin, D; Moorhead, C; Devlin, A
Abstract : Rapidly advancing practice and recognition of nursing, midwifery and medicine as a vital interrelated workforce, implies a need for a variety of curricula opportunities. This project addresses the challenge for healthcare educators to widen student engagement and participation through inter-professional education by creating learning environments whereby student interactions foster the desire to develop situational awareness, independent learning and contribution to patient advocacy. Overall aim of this 'Feeding and Nutrition in Infants and Children' project is to provide opportunities for integrated learning to enable students to advance their knowledge and understanding of current best practice. This Inter-professional (IPE) student-lead workshop was initially implemented in 2006–07 in collaboration with the Centre for Excellence in IPE, within the curricula of medical and nursing programmes.¹ Supported by the development of a student resource pack, this project is now being offered to Learning Disability nursing and Midwifery students since September 2014. Methods: Fourth year medical students, undertaking a 'Child Healthcare module', alongside nursing and/or midwifery students are divided into groups with three or four students from each profession. Each group focuses on a specific feeding problem that is scenario-based on a common real-life issue prior to the workshop and then present their findings/possible solutions to feeding problem. They are observed by both facilitators and peers, who provide constructive feedback on aspects of performance including patient safety, cultural awareness, communication, decision making skills, teamwork and an appreciation of the role of various professionals in managing feeding problems in infants and children. Results: Participants complete a Likert-scale questionnaire to ascertain their reactions to this integrated learning experience. Ongoing findings suggest that students evaluate this learning activity very positively and have stated that they value the opportunity to exercise their clinical judgement and decision making skills. Most recent comments: 'appreciate working alongside other student's/multidisciplinary team approach' As a group students engage in this team problem-solving exercise, drawing upon their strengths and abilities to learn from each other. This project provides a crucial opportunity for learning and knowledge exchange for all those medical, midwifery and nursing students involved. Reference: Purdy J, Stewart M. Feeding and nutrition in infants and children: an interprofessional approach. Clin Teacher 2009;6(3)